The Effect of Foreign Exchange Forward Contracts on Bank Indonesia's Prudential Principles Report and Its Role in Moderating Exchange Rate Difference Profit and Loss - Lubis, Anggi Apriliani; Esti Riwayati, Hedwigis (Management Research Studies Journal, 2026)
This study aims to analyze the effect of foreign exchange forward contract utilization on compliance with Bank Indonesia’s prudential reporting principles and its role in moderating the relationship between forward contracts and corporate foreign exchange gains and losses at PT XX, an affiliated company of PT United Tractors Tbk. The research employs a quantitative approach using secondary data derived from the company’s financial statements and prudential compliance reports over a specific observation period. Data were analyzed using linear regression and moderated regression analysis to examine the relationships among the research variables. The results indicate that the utilization of foreign exchange forward contracts does not have a significant effect on compliance with Bank Indonesia’s prudential reporting principles. In addition, forward contract utilization has not shown a significant impact on the company’s foreign exchange gains and losses. Compliance with prudential reporting principles tends to moderate the relationship between forward contracts and foreign exchange gains and losses; however, the moderating effect is not statistically significant. These findings suggest that exchange rate risk management is not solely determined by the use of forward contracts but is also influenced by other factors, such as exchange rate volatility and overall economic conditions. This study is expected to provide insights for companies in managing foreign exchange risk and improving the quality of prudential reporting practices.